2021
DOI: 10.3390/life11080755
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Hungarian MODY Patients—Part I: Gene Panel Sequencing Reveals Pathogenic Mutations in HNF1A, HNF1B, HNF4A, ABCC8 and INS Genes

Abstract: Maturity-onset diabetes of the young (MODY) has about a dozen known causal genes to date, the most common ones being HNF1A, HNF4A, HNF1B and GCK. The phenotype of this clinically and genetically heterogeneous form of diabetes depends on the gene in which the patient has the mutation. We have tested 450 Hungarian index patients with suspected MODY diagnosis with Sanger sequencing and next-generation sequencing and found a roughly 30% positivity rate. More than 70% of disease-causing mutations were found in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Pathogenic or likely pathogenic variants in ABCC8 are present in about 15% of individuals with neonatal diabetes and in some 2% of patients with MODY-monogenic diabetes ( De Franco et al, 2015 ; Gaál et al, 2021 ; Rafique et al, 2021 ). With regard to diabetic kidney disease, microalbuminuria was indeed observed in some patients with ABCC8 -MODY12.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic or likely pathogenic variants in ABCC8 are present in about 15% of individuals with neonatal diabetes and in some 2% of patients with MODY-monogenic diabetes ( De Franco et al, 2015 ; Gaál et al, 2021 ; Rafique et al, 2021 ). With regard to diabetic kidney disease, microalbuminuria was indeed observed in some patients with ABCC8 -MODY12.…”
Section: Discussionmentioning
confidence: 99%
“…Elsősorban azokban a betegségekben indokolt az NGS használata, ahol több gén érintettsége is felmerül. Különösen fontos ez az endokrinológiában a nemi mirigyek alulműködésének azon genetikailag meghatározott formáiban, ahol a gond az ezeket szabályozó agyi központokban (elsősorban a hipotalamuszban) található (hipogonadotróp hipogonadizmus) (Butz et al, 2021), a cukorbetegség ritka formáiban (Gaál et al, 2021) és e cikkgyűjtemény egy másik cikkében bemutatott feokromocitóma/paraganglióma (Perge-Igaz, 996-1004. ) genetikai hátterének vizsgálatában (Sarkadi et al, 2021).…”
Section: úJgenerációs Szekvenálási Technikák éS Szekvenáló Rendszerekunclassified
“…Another vital role of HNF4α is the regulation of metabolic homeostasis. Most HNF4α-related diseases have abnormal insulin secretion such as occurrence of diabetes mellitus (including Type I and Type II diabetes mellitus), while the underlying molecular mechanism remains elusive ( 6 , 7 ). It has been shown that HNF4α interacts with Circadian Locomoter Output Cycles Protein Kaput (CLOCK)/BMAL1 to regulate a series of metabolic genes involved in lipid, glucose and amino acid homeostasis.…”
Section: Introductionmentioning
confidence: 99%